A novel corrugated steel plate-rubberized concrete composite slab: Properties and application opportunities. (September 2022) - Li, Fang; Liu, Baodong; Sun, Haibo; He, Wentao; Wang, Xiaoxi
Abstract: An innovative type of corrugated steel plate-rubberized concrete (CSPRC) composite slab is presented in this paper. This kind of composite slab can be applied to projects with energy consumption requirements in bridge deck slabs in potential rockfall regions, protective structures, defensive walls, military structures, and so on. Four specimens were executed to push out the test. Six full-scale CSPRC composite slab specimens were fabricated, two of which were dynamically tested and four of which were statically tested. The experimental results show that rubberized concrete inhibited the development of concrete cracks and improved the ductility of the specimens compared to normal concrete. The shank length of the stud shear connectors had a significant influence on the shear resistance. For this structure, the stud spacing had a higher requirement of 8.5 d than that of conventional composite beams. The longitudinal shear bearing capacity was not affected by incorporating rubber in the composite slab, and the failure loads and behaviors were similar to those of normal concrete. Additionally, the damping ratio and kinetic energy were improved. Based on the experimental and partial shear connection (PSC) methods, the calculation formulas for longitudinal shear strength were further revised and compared with current codes and test results to properly estimate the longitudinal shear capacity of the CSPRC composite slab.